IMPLEMENTATION OF WEB-BASED COMMUNITY HEALTH SERVICE APPLICATIONS: A LITERATURE REVIEW - Ananda Mutia Dewi; Ainol Mardiah; Arista Ardilla; Esar Alkausar (PT. Radja Intercontinental Publishing, 2024)
This study examines the use of web-based applications in Community Health Centers (Puskesmas) in Indonesia, focusing on their impact on healthcare services. The research identifies the types of healthcare services implemented through web-based applications and evaluates their effectiveness in improving healthcare delivery. A systematic literature review was conducted following the PRISMA method, with an initial search of 30 articles published from 2020 to 2024. After applying inclusion and exclusion criteria, 14 articles were selected for final analysis. The results indicate that web-based applications, such as telemedicine and electronic health records, have enhanced the efficiency, accessibility, and management of services at Puskesmas. However, challenges such as infrastructure limitations, lack of standardized policies, digital literacy, and data security must be addressed. The study concludes that integrating various healthcare services into a single web-based platform could improve service delivery and outcomes at Puskesmas. These findings provide valuable insights for policymakers and technology developers in enhancing healthcare systems.